The role of trabeculectomy in the era of minimally invasive glaucoma surgery. Issue 2 (29th March 2022) - Kalarn, Sachin; Le, Tinh; Rhee, Douglas J.
Abstract : Purpose of review: This review discusses recent findings in surgical management of glaucoma, focusing on trabeculectomy and minimally invasive glaucoma surgery (MIGS). We discuss how the role these procedures play in conjunction with phacoemulsification. Recent findings: New findings of the Primary Trab Vs Tube study and findings regarding the Hydrus, Xen 45, Kahook dual blade, Ab-interno Canaloplasty and head-to-head MIGS studies are summarized. Summary: Patients with glaucoma greatly benefit from combining cataract surgery with a MIGS procedure that can be tailored to disease severity and medication use. Certain MIGS combined with phacoemulsification in severe and refractory glaucoma can potentially delay incisional glaucoma, although trabeculectomy- mitomycin C (MMC) still remains the best option in certain patient populations. We provide an update in the MIGS treatment paradigm based on newer, stronger evidence.